CRISPR screen decodes SWI/SNF chromatin remodeling complex assembly - Hanna Schwaemmle; Hadrien Soldati; Nikolaos M. R. Lykoskoufis; Mylène Docquier; Alexandre Hainard; Simon M. G. Braun (Nature Communications)
Abstract The SWI/SNF (or BAF) complex is an essential chromatin remodeler, which is frequently mutated in cancer and neurodevelopmental disorders. These are often heterozygous loss-of-function mutations, indicating a dosage-sensitive role for SWI/SNF subunits. However, the molecular mechanisms regulating SWI/SNF subunit dosage to ensure complex assembly remain largely unexplored. We performed a CRISPR KO screen, using epigenome editing in mouse embryonic stem cells, and identified Mlf2 and Rbm15 as regulators of SWI/SNF complex activity. First, we show that MLF2, a poorly characterized chaperone protein, promotes SWI/SNF assembly and binding to chromatin. Rapid degradation of MLF2 reduces chromatin accessibility at sites that depend on high levels of SWI/SNF binding to maintain open chromatin. Next, we find that RBM15, part of the m6A writer complex, controls m6A modifications on specific SWI/SNF mRNAs to regulate subunit protein levels. Misregulation of m6A methylation causes overexpression of core SWI/SNF subunits leading to the assembly of incomplete complexes lacking the catalytic ATPase/ARP subunits. These data indicate that targeting modulators of SWI/SNF complex assembly may offer a potent therapeutic strategy for diseases associated with impaired chromatin remodeling.